Answer:
3
Step-by-step explanation:
f(x)=a*b^x - is a formula of exponential function
As we know the point (x=0; y=3) lies at the function's graph.
So we have to put in formula f(x)=a*b^x x=0 f(x)=y=3
3=a*b^0 (b^0=1) => 3=a*1 => 3=a
Answer:
Step-by-step explanation:
-2(4-3x)+(5x-2)
-8+6x+5x-2
11x-10
Answer:
≈ 78.55 cm
Step-by-step explanation:
Using the ratio of arc (AB) to circumference (C) is equal to the ratio of angle subtended at centre by arc AB to 360°, that is
=
, that is
=
( cross- multiply )
110C = 8640 ( divide both sides by 110 )
C =
≈ 78.55 cm ( to 2 dec. places )
Answer:-47 3/4
Step-by-step explanation:
The correct answer would be -47 3/4
You would use the equation
-32 1/4 - 15 1/2 = -47 3/4
to find your answer